Detection and genome sequencing of porcine circovirus 3 in neonatal pigs with congenital tremors in South China. Issue 6 (3rd October 2017) - Chen, G. H.; Mai, K. J.; Zhou, L.; Wu, R. T.; Tang, X. Y.; Wu, J. L.; He, L. L.; Lan, T.; Xie, Q. M.; Sun, Y.; Ma, J. Y.
Summary: Porcine circovirus 3 (PCV3) is a novel circovirus first discovered in the United States in piglets and sows with porcine dermatitis and nephropathy syndrome, reproductive failure, cardiac and multisystemic inflammation. Here, seven PCV3 strains were identified for the first time from neonatal pigs with clinical signs of congenital tremors (CT) in South China. The tissue tropism of PCV3 in CT‐affected piglets was analysed by the real‐time quantitative PCR, and the result showed that high loads of viral genomes were detected in the brains and hearts. The complete genomes of seven new PCV3 revealed 96.8%–99.6% nucleotide identities with eleven other PCV3 strains previously reported from the United States and China. Phylogenetic analysis based on the complete genome sequences showed that all PCV3 strains clustered together and were clearly separated from other circovirus species. This study reports on the first identification of PCV3 in CT‐affected newborn piglets and provides the epidemiological information of neonatal piglets with CT in Guangdong and Guangxi Provinces of China.